On Necessary Individuals and Ways (sic!) for Them to Be: Celebrating 10-Year Anniversary of Modal Logic as Metaphysics. - Gricius, Pranciškus (Problems / Problemos, 2023)
The article "On Necessary Individuals and Ways (sic!) for Them to Be: Celebrating 10-Year Anniversary of Modal Logic as Metaphysics" features an interview with Timothy Williamson, a prominent figure in contemporary analytic philosophy. The discussion revolves around modal logic, Saul Kripke's work, the controversy between necessitists and contingentists, higher-order logics, and metaphysics. Williamson argues for necessitism and explains the importance of higher-order logics in understanding metaphysical concepts. The article highlights the shift towards broader themes and the development of higher-order metaphysics in philosophical inquiries. Readers interested in entering these fields are advised to master logic, approach philosophy as theorizing, and evaluate theories abductively, considering evidence and trade-offs between simplicity and strength.